"Like They've Never, Ever Seen in This Country"? Political Interest and Voter Engagement in 2016. (20th March 2018) - Prior, Markus; Bougher, Lori D
Abstract: Journalists and political pundits have characterized the 2016 presidential campaign as one featuring unusually high levels of political involvement among the mass public. This article subjects such claims to more systematic assessment, by comparing levels of political involvement in the 2016 presidential election campaign to those of previous election cycles. Through analyses of turnout statistics, survey questions by the Pew Research Center and the American National Election Studies measuring political interest, and Nielsen audience estimates of television viewing, the article finds that the public's interest and engagement in the fall of 2016 were actually quite similar to those of other recent elections. (It was during the primaries that political involvement in 2016 stood out more.) Acknowledging that aggregate analyses may obscure countervailing subgroup changes, the article examines subgroups that figured prominently in accounts of the 2016 campaign or were thought to have been particularly energized by Barack Obama in 2008 and 2012: men without a college education, African Americans, and young people. Those analyses turn up limited evidence for differential political interest trends. African Americans' campaign interest and turnout did drop compared to 2008 and 2012. But in the opposite direction of the prevailing narrative, young people showed relatively high political involvement.